2017
DOI: 10.3389/fpsyg.2016.02003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Working Memory Training among Subjects Currently on Sick Leave Due to Complex Symptoms

Abstract: Introduction: The current study examined if adaptive working memory training (Cogmed QM) has the potential to improve inhibitory control, working memory capacity, and perceptions of memory functioning in a group of patients currently on sick leave due to symptoms of pain, insomnia, fatigue, depression and anxiety. Participants who were referred to a vocational rehabilitation center volunteered to take part in the study.Methods: Participants were randomly assigned to either a training condition (N = 25) or a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 75 publications
(94 reference statements)
1
14
0
Order By: Relevance
“…Although the patient groups in the above studies share overlapping work and health characteristics with the patients in the present study, it is challenging to interpret these results because the RTW or healthcare interventions do not seem comparable. However, in a comparable setting, individuals going through occupational rehabilitation and receiving working memory training have been found to improve more in inhibiting prepotent responses, but not spatial working memory, compared to individuals receiving treatment as usual (Aasvik et al, 2017). This may indicate that adding an extra intervention focusing on cognitive training may improve certain functions more than others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the patient groups in the above studies share overlapping work and health characteristics with the patients in the present study, it is challenging to interpret these results because the RTW or healthcare interventions do not seem comparable. However, in a comparable setting, individuals going through occupational rehabilitation and receiving working memory training have been found to improve more in inhibiting prepotent responses, but not spatial working memory, compared to individuals receiving treatment as usual (Aasvik et al, 2017). This may indicate that adding an extra intervention focusing on cognitive training may improve certain functions more than others.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that improvements in focused attention were associated with a reduction in SHC related to pseudoneurological complaints indicate that attentional mechanisms were influenced by several factors. Moreover, the application of various forms of cognitive training in chronic pain (Baker et al, 2018), depression (Jonassen et al, 2019) and on patients in occupational rehabilitation (Aasvik et al, 2017) has shown promising effects on cognitive functioning and clinical symptoms. The treatment components in occupational rehabilitation do influence cognitive functioning as shown in the present study, making it relevant to assess possible improvements in cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Borella, Carretti, Riboldu & De Beni ( 2010 ) demonstrated that working memory training led to improvements in inhibition in older adults (65–75 years). Notably, Aasvik et al ( 2017 ) reported that WM training improved inhibition in a group of participants who were on sick leave due to complex issues (including depression and anxiety). These findings are consistent with neuroimaging evidence that working memory and inhibitory tasks both activate the ventrolateral prefrontal cortex, which might reflect the neural basis for transfer between working memory and inhibition (McNab et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%